Influência da proporção de vegetação nativa e da heterogeneidade da paisagem na paisagem sonora do Alto Paranapanema - Araújo, Júlio Cesar Lima (Universidade Federal de São Carlos, 2023)
Land use intensification alters spatial patterns, homogenizing landscapes and limiting native vegetation to areas of low agricultural suitability. Despite being a process that has advanced throughout the tropical region, there is still much to learn about its effects on the composition and diversity of species that occupy these landscapes. In this study, I present two chapters in which: I) I use diversity and acoustic complexity as indicators of biological diversity and assess how these metrics relate to different proportions of native vegetation and degrees of heterogeneity, and II) how the proportion of native vegetation influences the richness and composition of the anuran fauna in the sampled landscapes. The results show a negative relationship between acoustic diversity and the proportion of native vegetation, while for acoustic complexity, the relationship was positive, but varied depending on the heterogeneity of the landscapes. In landscapes with higher heterogeneity, the effects of the proportion of native vegetation are greatly reduced; however, in more homogeneous landscapes, the influence of the proportion of native vegetation is strong. The anuran fauna showed an influence of the proportion of native vegetation on its richness and, especially, on the composition of the communities, with a high sharing of species in smaller proportions and a greater number of exclusive species within continuous forests. This study provides important information for biodiversity conservation in altered landscapes, contributing to the management of multifunctional landscapes that reconcile biodiversity and agricultural production.
Influence of native vegetation proportion and landscape heterogeneity on the soundscape of Alto Paranapanema
Keywords: Índices acústicos; Anuros; Homogeneização da paisagem; Vegetação nativa; Mata Atlântica; Acoustic index; Anurans; Landscape homogenizing; Native vegetation; Atlantic forest; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS